Perception of modern technologies by the older generation: comparative analysis - T. A. Aimaletdinov; M. V. Tsimbal (Цифровая социология, 2024)
This article discusses the empirical research results devoted to the study of the older generation attitude to modern technologies: fears, expectations, and motivation to use such technologies. The obtained results are interpreted through a humanistic paradigm, in which technologies are considered as a tool for realising human potential, in particular, the potential of the older age group. In the course of the study, a comparative analysis was conducted by gender and age groups. The main conclusions drawn from the scientific work results are as follows. Firstly, it is the older generation that assumes the role of “technological optimists”, unlike younger and middle-aged people who have more concerns about the development of information technology. This applies both to everyday life and to the national problems of the increment of scientific knowledge. Secondly, the older generation noticeably need the humanistic aspect of technology more. This includes distrust of full automation, for example, driverless cars, as well as the need for a tutor and mentor when mastering new technologies. At the same time, it is the elderly generation that expresses the greatest trust in people around them. Thirdly, in many respects, the older generation has more similarities in their expectations and preferences with the younger age group than with those who are closer to them in age.